Effects of Vacuuming Mattresses on Allergic Rhinitis Symptoms in Children - Jeon, You Hoon; Lee, Yong Ju; Sohn, Myung Hyun; Lee, Hae Ran (Allergy, asthma & immunology research, 2019)
To evaluate the effects of daily vacuuming of mattresses on the concentration of house dust mite (HDM) allergens and on allergic rhinitis (AR) symptoms in children sensitized to HDM. Forty children between the ages of 6 and 12 years with mild persistent AR and sensitized only to HDM were enrolled and randomly allocated to 2 groups. Caregivers of children in the experimental group cleaned the children's rooms and vacuumed their mattresses daily for 2 weeks. Caregivers of children in the control group cleaned the children's rooms without vacuuming mattresses. Symptoms of AR were checked weekly and dust samples were collected from the mattresses before and after the study. Demographics at the beginning of the study were not significantly different between the 2 groups. In the experimental group, symptoms of AR and dust weight were significantly decreased after 2 weeks (total symptoms of AR, <0.001; sneezing, < 0.001; rhinorrhea, <0.001; nasal obstruction, < 0.001; itching, <0.001; and dust weight, = 0.006). The concentrations of HDM allergens were not changed significantly (Der p1, = 0.333; Der f1, = 0.841). In the control group, there were no significant changes in symptoms of AR, dust weight, or the concentration of HDM allergens. Our findings showed that daily vacuuming of mattresses reduced dust weight and symptoms of AR. However, the concentration of HDM allergens did not significantly decrease.